Quasi-two-dimensional perovskite light emitting diodes for bright future - Jin-Wook Lee; Nam-Gyu Park (Light: Science & Applications, 2021)
Abstract The fundamentals, promise and challenges of metal halide quasi-two-dimensional (quasi-2D) perovskites for a next generation emitter in light emitting diode devices are systematically reviewed.